Incidencia del cancro cítrico (Xanthomonas citri) en el cultivo de naranja (Citrus sinensis) en el Ecuador - INDACOCHEA CARRASCO, OSWALDO VLADIMIR (2023)
In the phytosanitary field, one of the major limitations detected in orange crop production is the presence of the citrus canker disease caused by the bacterium X. citri, which is distributed in some countries of the world with greater indecency and severity; although in Ecuador there are still no evident reports of the presence of the disease in orange plantations, and it is important to consider this disease as a quarantine pest. The information obtained was paraphrased, summarized and analyzed in order to obtain relevant information on the incidence of citrus canker (X. citri) in the orange crop (C. sinensis) in Ecuador. From the above, it was determined that citrus canker is a disease that can occur throughout the year, affecting seedlings and young trees, which have a high production of vegetative shoots. The symptoms on the leaves are young lesions with a yellow halo and wet edges, which disappear with age; the lesions measure about 2-10 mm, although in favorable situations they unite and affect larger areas. The disease can cause extreme defoliation, branch death and premature fruit drop; the latter can also lose their commercial cost due to damage to the peel. The X. citri bacterium is spread with the help of water present on the surface of the foliage, which drips and splashes the new shoots; the bacteria in the water depends on the age of the lesion and varies between one hundred-1000 million bacterial cells consisting of droplets. Control measures for citrus canker disease (X. citri) in orange cultivation involve various activities such as exclusion, eradication, integrated control and disinfection.